Susceptibility Weighted Imaging in Migraine with and Without Aura: A Case–Control Study - Scutelnic, Adrian; Klail, Tomas; Moor, Diego; Slavova, Nedelina; Petroulia, Valentina; Jung, Simon; Branca, Mattia; Fischer, Urs; Riederer, Franz; Wiest, Roland; Schankin, Christoph (Neurology international, 2025)
Background: The asymmetry of cortical veins in susceptibility weighted imaging (SWI) in MRI might be a biomarker for migraine aura and cortical spreading depression (CSD). The aim of this study was to assess in humans if SWI asymmetry can be found in patients who have migraine attacks without aura. Methods: We included patients (n = 100 per group) from the emergency room setting when they (i) presented with an acute neurological deficit or headache; (ii) had a discharge diagnosis of a migraine aura, a migraine without an aura, or neither (controls without stroke or epilepsy); and (iii) had a brain MRI with SWI in the acute setting. Results: In the migraine with aura group, SWI asymmetry was found in 26% (95% CI 18–35) compared to patients with migraine without aura (3%, [95% CI 1–8], p < 0.001) and controls 7% [95% CI 3–14], p < 0.001). There was no difference between patients with migraine without aura and controls (p = 0.19). Conclusions: The distinct SWI changes in migraine with and without aura suggest that CSD might not be involved in the pathophysiology of migraine without aura.